2020
DOI: 10.1016/j.ijid.2020.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value and dynamic variance of serum antibody in coronavirus disease 2019

Abstract: To investigate the diagnostic value of serological testing and dynamic variance of serum antibody in coronavirus disease 2019 . Methods: This study retrospectively included 43 patients with a laboratory-confirmed infection and 33 patients with a suspected infection, in whom the disease was eventually excluded. The IgM/IgG titer of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was measured by chemiluminescence immunoassay analysis. Results: Compared to molecular detection, the sensitivities of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
269
3
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(320 citation statements)
references
References 10 publications
21
269
3
16
Order By: Relevance
“…1A), while that of IgG remained stable at above 400 AU/mL after Day 13 ( Fig.1B). Similar dynamic changes were also reported by another study 7 . The timing when the median titers of IgM and IgG exceeded the manufacturer's cutoff value (10 AU/mL) were Day13-14 and Day9-10, respectively, which might beare similar to those for severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1) 8 and slightly earlier than those for Middle East respiratory syndrome coronavirus (MERS-CoV) 9,10 .…”
Section: Discussionsupporting
confidence: 91%
“…1A), while that of IgG remained stable at above 400 AU/mL after Day 13 ( Fig.1B). Similar dynamic changes were also reported by another study 7 . The timing when the median titers of IgM and IgG exceeded the manufacturer's cutoff value (10 AU/mL) were Day13-14 and Day9-10, respectively, which might beare similar to those for severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1) 8 and slightly earlier than those for Middle East respiratory syndrome coronavirus (MERS-CoV) 9,10 .…”
Section: Discussionsupporting
confidence: 91%
“…Studies on SARS-CoV-1 showed that most patients seroconverted after infection but this was delayed (17-21 days) compared to a typical time course for seroconversion with other 325 respiratory viruses 30,31 . Several studies demonstrate seroconversion of IgG antibodies against the spike protein 1-3 weeks after infection with SARS-CoV-2 [32][33][34][35][36] 38 . Similarly, the median time for seroconversion to IgG in hospitalized patients was found to be 14 days in a study of 173 patients in China, with some taking up to 1 month to generate antibody detectable in a commercial ELISA test 39 .…”
Section: The Relationship Between Seroprevalence and Sars-cov-2 Exposmentioning
confidence: 99%
“…11 The aim of the this study was to assess the diagnostic performance of a novel fully automated CLIA for the quantitative detection of anti-SARS-CoV-2 IgM and IgG antibodies. [12][13][14][15] However, it is unclear which antibodies are optimally effective in the scenario of COVID-19 and which of them are neutralizing. There is also uncertainty as to which antibody isotype (IgM, IgG or IgA) (single or combined) is the best choice in these different contexts.…”
mentioning
confidence: 99%